Method for Modeling the Small Intestine and Resident Microbiome Through in Vitro Fermentation (P20-001-19). (13th June 2019) - Doherty, Laurel; Whitman, Jordan; Arcidiacono, Steven; Conca, Karen; Soares, Jason
Abstract: Objectives: The human small intestine is a complex and dynamic organ tasked with enzymatic digestion and absorption of nutrients. Design of a small intestine model can provide detailed systematic knowledge of these processes; model design challenges include differential pH and oxygen availability along the length of the small intestine, food-dependent host secretion of digestive compounds, complex nutrient absorption processes, and microbiome interactions with both food and host. Numerous in vitro models have been developed to simulate the small intestine, but physiological relevance is limited. Here, we present an in vitro fermentation model of the small intestine to include microbiota and enhance physiological relevance. Methods: A stepwise biofidelic model design approach was implemented with initial stages consisting of simulating ileum conditions, including pH and residence time, utilizing an automated bioreactor system for real-time monitoring and control of fermentation parameters, with incorporation of digestive enzymes and bile acids for breakdown of food inputs. Nutrient absorption, simulated using hollow-fiber columns to emulate passive diffusion, was initially optimized using small molecules to mimic dietary digestion byproducts; validation with food components, such as starch or whey powder, is planned. A mock microbial community, with organisms selected to represent major phyla and functions of the small intestine microbiota, was designed, implemented, and characterized in fermentations representing "fed-state" ileum conditions. Results: Design and validation of the model with mock food components will be presented, along with steps taken to integrate in situ nutrient absorption and mock microbial community. Initial characterization of the microbial community indicates synergistic growth dynamics and nutrient utilization under "fed-state" conditions. Conclusions: These efforts will be the foundation for our long-term goal of simulating the small intestine to complement our large intestine fermentation model, jA 2 COB, creating a complete in vitro fermentation model of the lower GI tract. Insight gleaned from this model, alone or in concert with in vivo studies, can inform nutritional strategies to restore and maintain host gut homeostasis. Funding Sources: Funded by U.S. Army NSRDEC core applied research funds.